Improving the Quality of Life of People with Disability through Zakat: A Zakat Utilization Model Canvas Perspective - Sari, Aisha Putrina; Anggraini, Dita; Junari, Ulfah Lathifah (AL-MUZARA'AH, 2024)
Islam upholds the principle of equality for all individuals, regardless of their disability status. The sole distinction between people lies in their level of piety. However, in reality, people with disabilities (PWD) continue to face various forms of discrimination, ranging from education and employment to societal stigma, hindering their ability to improve their quality of life. Furthermore, the exclusion of PWD from the economy can result in a national GDP loss of up to 7% per year. Zakat optimization presents a potential solution to enhance the lives of PWD. In this context, PWD can be classified under the asnaf of fakir (the poor) and/or miskin (the destitute). Their categorization as fakir stems from their limitations in meeting basic needs, while their classification as miskin is supported by data and research indicating a strong correlation between disability and poverty. Unfortunately, the attention given to PWD within the zakat system remains relatively low. Therefore, employing a qualitative research methodology, this paper delves into the distribution of zakat in the disability sector and proposes an integrated distribution model for PWD. This model entails grouping PWD based on their age and work capabilities before providing appropriate assistance. Additionally, utilizing the Zakat Utilization Model Canvas (ZUMC), this paper explores the ideal planning framework for disability programs that can be implemented by zakat institutions. ZUMC adopts a holistic approach, considering not only the commercial aspects of programs but also the empowerment of mustahik (zakat recipients) in each element. This paper aims to contribute to the still-limited research on zakat and disability in Indonesia.